Preferensi Peternak terhadap Bangsa Ternak Babi Rakyat: Studi Kasus di Desa Tasinifu Kecamatan Mutis Kabupaten Timor Tengah Utara - Hoar, Fransiska; Sahala, Josua; Feka, Wolfhardus Vinansius; Banu, Marselinus; Magdalena Kapitan, Maria; Wilfrida Kolo, Maria; Deasni Seran, Vianey (JURNAL RISET RUMPUN ILMU HEWANI, 2026)
As an agricultural country, Indonesia is able to meet the demand for animal protein in the form of meat. Pigs are a potential business opportunity for some people because they are a promising livestock business. The study aims to determine the characteristics of livestock farmers and preferences for pig livestock in Tasinifu Village, Mutis District, North Central Timor Regency. This study was designed using a survey method. The technique for determining the research location used a purposive technique (intentionally) because Tasinifu Village is a village that has the highest pig population in Mutis District, TTU Regency. Data analysis was done using a quantitative descriptive method. The results of the study showed that livestock farmers were aged 18-40 years (31.67%), female farmers (55%), the highest level of education was elementary school (61.67%), the highest number of family dependents was 4-6 people (23.33%), livestock experience was 2-10 years (95%), dominant livestock ownership was 2-5 pigs with the majority of farmers working as farmers (97%), with land area owned 0-025/ha (66.67%). Pigs aged 5-7 months (41.67%), the most commonly raised breed is the Timor pig (75%), with female Calamine (58.33%), black skin (55%), and medium body weight (80%). The livestock raising sistem is intensive (80%), and the use of feed and agricultural waste (62%).